Variation in Odour Profiles of Cauliflower, Curly Kale and Broccoli (Brassica oleracea L.) Cultivars Is Affected More by Genotype Rather than Herbivore Feeding - Raimondas Mozūraitis; Peter Hambäck; Anna-Karin Borg-Karlson; Richard James Hopkins (Plants)
Volatile plant compounds are essential for host plant selection by herbivores and particularly important for the behaviour of parasitoids seeking larvae in which to lay eggs. Headspace extracts were collected from intact plants of four Brassica oleracea genotypes, as well as from plants damaged by larvae of Mamestra brassicae or Pieris rapae. In total, 52 volatiles present in the headspaces of four genotypes were selected for multivariate analyses. The most abundant groups of volatiles were terpenes and esters, represented by 20 and 14 compounds, respectively. The qualitative and quantitative differences in odour profiles between the four genotypes were sufficient to differentiate between groups using multivariate analysis techniques. The most distinct volatile blends originated from curly kale, followed by cabbage, cauliflower and broccoli. Multivariate analysis revealed that genotypes affected the composition of the volatile blends to a large extent compared to the herbivore damage by the different species tested. In curly kale, broccoli and cauliflower, the differences in odour bouquets were more expressed between plants with and without active feeding, independent of the herbivore identity, while in cabbage, larger differences were observed between odour profiles with different herbivore feedings, independent of whether the herbivore was present or removed.